2017
DOI: 10.1111/jam.13526
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity and modes of LI-F type antimicrobial peptides againstBacillus cereus in vitro

Abstract: The results of this study provide a theoretical basis for utilizing AMP-jsa9 or similar analogues as natural and effective preservatives in the food and feed industries. These efforts could also stimulate research activities interested in understanding the specific effects of other antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…These results demonstrated that both plantaricin GZ1-27 and nisin increased the permeability of the B. cereus cell membrane, which led to the efflux of K + . Similar results were reported for antimicrobial peptide F1, 32 antimicrobial peptide AMP-jsa9, 20 lactosporin, 33 and two-peptide (LtnA1 and LtnA2). 34 Effect of Plantaricin GZ1-27 on the Integrity and Viability of B. cereus Cells.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results demonstrated that both plantaricin GZ1-27 and nisin increased the permeability of the B. cereus cell membrane, which led to the efflux of K + . Similar results were reported for antimicrobial peptide F1, 32 antimicrobial peptide AMP-jsa9, 20 lactosporin, 33 and two-peptide (LtnA1 and LtnA2). 34 Effect of Plantaricin GZ1-27 on the Integrity and Viability of B. cereus Cells.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…After centrifugation at 5000 × g for 10 min (4 °C), the supernatants were filtered through 0.22 μm filters and the K + concentrations were measured on an Optima 8000 plasma atomic emission spectrometry (PerkinElmer Inc., Waltham, MA). 20 Flow Cytometry. Bacterial membrane integrity was assayed by measuring the uptake of propidium iodide.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The SEM examination was carried out using the method of Han et al. (2017). Compound 3 was treated with B .…”
Section: Methodsmentioning
confidence: 99%
“…The viable counts of tested bacteria were determined based on J Han's detection method (Han et al, 2017). The FC at the MIC level was used to inoculate a bacterial suspension containing 10 7 CFU/ml and incubate at 37 °C with a 150 r/min shaking incubator for viable bacteria count.…”
Section: Antibacterial Potentialmentioning
confidence: 99%